HUBUNGAN PERILAKU IBU DENGAN KEJADIAN ISPA PADA BALITA DI DESA JABON KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Sinthia Ariska Gahiwu; Dwi Helynarti Syurandhari (MEDICA MAJAPAHIT, 2024)
ISPA Disease in Indonesia ISPA disease is the first highest cause of death in infants and morbidity in toddlers. In addition, this disease is often in the top 10 diseases in health facilities, especially at the Puskesmas. The aim of this research was to find out the behavior of mothers with the incidence of ARI in toddlers in Jabon Village, Mojoanyar District, Mojokerto Regency. This type of quantitative research uses an observational method with a cross sectional approach. The sample in this study were mothers who had toddlers in Jabon Village, Mojoanyar District, Mojokerto Regency. A total of 55 people by taking samples using Simple Random Sampling. The results of research on the relationship between mother's behavior and ISPA incidence in toddlers in Jabon Village, Mojoanyar District, Mojokerto Regency. The results of the chi square statistical test showed a significant level of 0.052 < (0.05) for knowledge, a significant level of 0.058 (.0.05) for attitudes and a significant level of 0.611 for action, so knowledge had a relationship and attitudes and actions had no relationship with events ISPA. It is hoped that the community and research sites can provide a reference for increasing knowledge, attitudes and actions. For the author, it is hoped that this can become insight, information, used as a reference for continuing research